Analysis of lactic acid elevation in whole blood and blood pressure with work fatigue to airport apron work productivity - Datu I.E. Fatih; Syamsiar S. Russeng; Lalu M. Saleh; Yahya Thamrin; M. Furqaan Nai’em; Anwar Mallongi; Saimi Saimi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The occupational safety and health of airport apron workers is very important. Occupational safety protection and policies are indispensable. Methodology: This study aims to analyze the increase in lactic acid in whole blood and blood pressure with work fatigue on work productivity. Analytical observational quantitative research. Sample of 40 people. Lactic acid measurement through blood sampling is measured using an acquired lactate plus lactate meter (mmol/L), and blood pressure is measured using a Tension meter (mmHg). Fatigue and productivity data were collected using a subjective self-rating test questionnaire from the industrial fatigue research committee. Results: Increase in lactic acid, obtained correlation value (r) 0.623 (0.51-0.75), Increased lactic acid leads to work fatigue. In the relationship of lactic acid to productivity, A correlation of value (r) -0.552 (0.51-0.75) was obtained. Increased lactic acid, does not affect the decrease in work productivity. Increased blood pressure obtained value (r) 0,661(>0,51-0,75), can cause work fatigue. Blood pressure with a negative correlation value (r) - 0.669 (0.51-0.75, does not affect productivity. The relationship between work fatigue and work productivity, there is a positive correlation relationship obtained value (r) 0.638 (0.51-0.75), Work fatigue which will have an impact on reducing work productivity. Conclusion: Increased lactic acid and blood pressure as a cause of work fatigue, and work fatigue as a cause of decreased work productivity.